Hall ion source with ballistic and magnetic beam focusing - Bizyukov, A.A.; Girka, A.I.; Sereda, K.N.; Nazarov, A.V.; Romaschenko, E.V. (Вопросы атомной науки и техники, 2008)
Reversible magnetic system for the circular Hall ion source with ion beam ballistic focusing was contrived and then investigated both theoretically and experimentally. It was shown that simultaneous application of ballistic and reversible magnetic focusing systems allows achieving ion beam compression from initial diameter of 100 mm to the 1 mm diameter in a plane of the crossover.